Correlation of Glasgow Coma Scale with Non-Contrast Computed Tomography findings in immediate post traumatic brain injury - Agrawal, Basudev; Verma, Rupesh (International Journal of Research in Medical Sciences, 2019)
Background: This study was undertaken to correlate Glasgow Coma Scale (GCS) score with Non-Contrast Computed Tomography (NCCT) findings in patients with acute traumatic brain injury (TBI) attending tertiary care Shree Narayana Hospital, Raipur, Chhattisgarh, India. Methods: A cross-sectional study was performed among 100 patients of acute traumatic head injury (those presenting to hospital within 24 hours of injury) over a period of six months. The patient’s GCS score was determined and NCCT Brain scan was performed in each case immediately (within 30 minutes) after presenting to casualty of the hospital. A 16 slice siemens Somatom CT scan was utilized and 5mm and 10mm sections were obtained for infratentorial and supratentorial parts respectively. Results: The age range of the patients was 0 to 76 years and male: female ratio was 2.85:1. Younger age group was more commonly involved, with 61% of cases seen in 11-40 years of age group. The most common causes of head injury were road traffic accident (RTA) (65%) and fall from height (25%). The distribution of patients in accordance with GCS was found to be 55% with mild TBI (GCS 12 to 14), 25% with moderate TBI (GCS 11 to 8) and 20% with severe TBI (GCS 7 or less). Conclusions: The presence of multiple lesions and midline shift on CT scan were accompanied with lower GCS, whereas patients having single lesion had more GCS level. There was significant correlation between GCS and NCCT findings in immediate post TBI.